A Comparison of the Distortion in the Same Field MRI and MR-Linac System With a 3D Printed Phantom - Liu, Xuechun; Li, Zhenjiang; Rong, Yi; Cao, Minsong; Li, Hongyu; Jia, Chuntao; Shi, Liting; Lu, Weizhao; Gong, Guanzhong; Yin, Yong; Qiu, Jianfeng (Frontiers in Oncology, 2021)
Purpose: The purpose of this study was to design and build a 3D printed geometric phantom that is able to be scanned by both CT and MRI and to use it to test geometric distortion and relevant dose changes of treatment planning systems. Materials and methods: The study was conducted using a self-designed 3D printed photosensitive resin phantom, which adopts grid-like structures and consists of 822 1cm2 squares. The scanning plan was delivered by three MRI scanners namely, the Elekta Unity MR-Linac 1.5T, the GE Signa HDe 1.5T and the GE Discovery-sim 750 3.0T. The most central transverse images of each dataset were selected to demonstrate the plane distortion. Besides, some marks points were selected to analyze the distortion in the three-dimensional direction based on plane geometric distortion. To study the effect of geometric distortion on radiotherapy measurement, the treatment plan was performed on the off-line Monaco system (TPS) (Elekta AB, Stockholm, Sweden). Results: After comparing normal and distorted values, it intuitively shows that the diffusion presents a spiral gradient from the center to the outside. The distortion range of the Unity is 0.80±0.40mm, the distortion value of the GE Signa HDe is 1.31 ±0.56 mm, while the distortion of GE Discovery-sim 750 was 2.82±1.48 mm. The distortion values of the Unity were smaller than GE Signa HDe no matter in plane-distortion or 3D distortion. In addition, the geometric distortion has little effect on the actual planning dose of radiotherapy as the doses for each region of interest were approximate.. Conclusion: From the center to the outside, the geometric distortion increases gradually and spreads in a spiral gradient. The final statistical analysis showed that the distortion values of Unity are smaller than GE Signa HDe, and Unity has the smallest geometric distortion and the dose variation that best matched the standard treatment plan.